Competitive Advantage Is Assessed From Entrepreneurial Orientation, Price Strategy And Location - Firman, Ahmad; Nianty, Dara Ayu; Sriyanti, Sriyanti (Program Studi Akuntansi Universitas Islam Lamongan, 2024)
The aim of this research is to examine the influence of entrepreneurial orientation, pricing strategy and location on competitive advantage. The method used in this research is a quantitative research method. The population in this study were MSMEs in Biringkanaya District, Makassar City with a total of 453 MSMEs. Biringkanaya District is the District recorded by the Department of Cooperatives and Small and Medium Enterprises in Makassar City as having the largest number of SMEs. The sample from this study used a purposive sampling method, in 2021-2023, so the total sample was 55 respondents. From the collected data, data analysis was then carried out using the SPSS (Statistical Package for Social Science) program. This analysis was carried out using several stages of multiple linear regression analysis to determine the magnitude of the influence that entrepreneurial orientation, pricing strategy and location have on competitive advantage. The research results found that both simultaneously and partially entrepreneurial orientation, pricing strategy and location had a positive and significant effect on competitive advantage